PSYCHOLOGICAL CHARACTERISTICS OF PATIENTS SUFFERING FROM SKIN DISORDERS: SKIN DISORDERS - Ishika Ghosh; Suchismita Sinha (STIKes Mandala Waluya Kendari, 2023)
Background: Dermatology holds a unique place among the other clinical specialties due to the